The book of Isaiah : Volume 3 Chapters 40-66 : the English text, with introduction, exposition, and notes - Young, Edward J. 1907-1968. (Edward Joseph) (Grand Rapids : Eerdmans, 1984)
A three-volume commentary which concentrates primarily on the meaning of the text of Isaiah, rather than on specific textual problems. This work is buttressed by the latest archaeological data, careful consideration of the Masoretic text, and a thorough understanding of the intellectual and cultural milieu in which the prophet lived. The commentator believes that Isaiah is the author of the entire prophecy, and it is in light of this belief that he seeks to interpret this portion of the Scriptures.
v. 1. Chapters 1 to 18.--v. 2. Chapters 19 to 39.--v. 3. Chapters 40 through 66.
Includes bibliographical references.
Keywords: Bible. -- Commentaries; Commentaries